Compression induces ephrin-A2 in PDL fibroblasts via c-fos: $hS. Sen, K. Diercke, S. Zingler, C. J. Lux, and R. Erber - Şen, Sinan; Diercke, Katja; Zingler, Sebastian; Lux, Christopher J.; Erber, Ralf (Journal of dental research, 2015)
Ephrin-A2-EphA2 and ephrin-B2-EphB4 interactions have been implicated in the regulation of bone remodeling. We previously demonstrated a potential role for memb...